Blindman's bluff - Kellerman, Faye (William Morrow imprint of HarperCollins, 2009)
Los Angeles detective Peter Decker tackles a homicide case involving a billionaire real estate developer, his wife, and four employees. While Decker leads his homicide team throughout California and into Mexico, he thinks his own wife is on jury back at the courthouse. But a chance encounter with a court translator who needs her help leads Rina into the heart of the murder investigation, and straight into the path of a gang of ruthless killers.